Protocol for the long‐term culture of human primary keratinocytes from the normal colorectal mucosa. Issue 7 (10th February 2019) - Torreggiani, Elena; Rossini, Marika; Bononi, Ilaria; Pietrobon, Silvia; Mazzoni, Elisa; Iaquinta, Maria Rosa; Feo, Carlo; Rotondo, John Charles; Rizzo, Paola; Tognon, Mauro; Martini, Fernanda
Abstract: Procedures for in vitro culturing of human primary keratinocytes from normal colon mucosa specimens have not been fully feasible, thus far. The protocol described herein allows primary keratinocytes from small tissue fragments of colorectal mucosa biopsies to grow in vitro. The procedure develops in three steps: (a) the enzymatic digestion of the tissue biopsy; (b) the use of cloning rings to purify primary keratinocyte colonies, (c) a defined keratinocyte medium to grow these cells in long‐term culture. Our cultural method enables normal primary keratinocytes to be obtained by simple and rapid techniques. In our culture condition, primary keratinocytes express specific epithelial markers. Colorectal mucosa keratinocyte colonies require approximately 2 weeks to grow. Compared with previous approaches, our protocol provides a valuable model of study for human primary keratinocytes from normal colorectal (NCR) mucosa both at the cellular and molecular levels. It is well known, that different mutations occurring during the multistep process of carcinogenesis in the NCR mucosa, are strictly associated to the onset/progression of the colorectal carcinoma. On this ground, normal keratinocytes grown with our protocol, may represent an innovative tool to investigate the mechanisms that lead to colorectal carcinoma and other diseases. Our innovative procedure may allow to perform comparative investigations between normal and pathological colorectal cells.